2011
DOI: 10.1002/macp.201100095
|View full text |Cite
|
Sign up to set email alerts
|

Selective Localization Behavior of Carbon Nanotubes: Effect on Transesterification of Immiscible Polyester Blends

Abstract: The selective localization of carbon nanotubes (CNTs) in an immiscible polymer blend has attracted much attention. If the two component polymers could react with each other, do selectively located CNTs affect those reactions? Here, an immiscible polyester blend based on polycarbonate/poly(trimethylene terephthalate) (PC/PTT) is studied. CNTs introduced during melt mixing are selectively located in the PTT phase and on the phase interface during the middle stage of melt mixing. The interface‐located CNTs can ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 51 publications
(65 reference statements)
0
33
0
Order By: Relevance
“…The preferential localization of MWCNT in PTT/PE blend system can be calculated thermodynamically from wetting coefficient, w a using the following Young's equation ωa=γfillerBγfillerAγAB where γfillerA, γfillerB, and γAB are the interfacial energies between filler and first polymer, filler and second polymer, and interfacial energy between the two polymers, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The preferential localization of MWCNT in PTT/PE blend system can be calculated thermodynamically from wetting coefficient, w a using the following Young's equation ωa=γfillerBγfillerAγAB where γfillerA, γfillerB, and γAB are the interfacial energies between filler and first polymer, filler and second polymer, and interfacial energy between the two polymers, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The surface energy of PTT and PE at 230 °C can be calculated from the known surface energy values of corresponding components using the equation γ=γ0(1TTc)119 where γ0 is the surface energy at 0 K, T is the temperature, and T c is the critical temperature (≈1000) . Surface energies of PTT at 25 °C, PE at 180 °C,and MWCNT at 20 °C obtained from the literature are tabulated in Table . Surface energy values calculated for PTT and PE at the processing temperature (at 230 °C) using Equation is shown in Table .…”
Section: Resultsmentioning
confidence: 99%
“…The value of the wetting coefficient in Table 2 further confirms the preferred location of TiO 2 in PLA. It has generally been reported that the nanoparticles would preferably locate in the polymer which has the lowest viscosity at the mixing temperature [9,22,26,28], but in this case it seems as if the interfacial interaction played a much more dominant role in determining the preferable location of TiO 2 in PLA/PCL blends. Figure 2 and Table 3 show the TGA results of all the investigated samples.…”
Section: Characterizationmentioning
confidence: 93%
“…Most of the time the nanofiller will selectively localise in one of the two blend phases in the blend, on the interface, or in one phase and on the interface. This selective localisation of the filler is controlled by differences in melt viscosity and affinity, the latter of which is closely related to the surface properties of the different components [25][26][27].…”
Section: A N U S C R I P Tmentioning
confidence: 99%
“…# a has been widely used to predict the thermodynamic equilibrium distribution of nanofillers in polymer blends [25,40]. Generally, for # a > 1, TiO 2 particles are only found in PU; for # a < -1, TiO 2 particles are present only in PLLA and for -1#< # a < 1, TiO 2 particles are selectively located at the interface between PLLA and PU.…”
Section: Differential Scanning Calorimetry (Dsc)mentioning
confidence: 99%